2008
DOI: 10.1111/j.1462-2920.2008.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and diversity of coral‐associated Archaea and their possible role in the coral holobiont nitrogen cycle

Abstract: Diversity, distribution and genetic comparison of Archaea associated with the surface mucus of corals from three genera, namely Acanthastrea sp., Favia sp. and Fungia sp., from the Gulf of Eilat, Israel and from Heron Island, Australia were studied. Sequencing of the 16S rRNA gene of the coral-associated Archaea revealed dominance of Crenarchaeota (79%, on average). In this phylum, 87% of the sequences were similar (>or= 97%) to the Thermoprotei, with 76% of these being similar (>or= 97%) to the ammonium oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 51 publications
1
164
1
1
Order By: Relevance
“…Among the Crenarchaeota, which are often the dominant archaeal group in marine samples, Thermoprotei was the only class represented and accounted for only 0.03 % of sequences. This phylum includes members that have previously been shown to form associations with coral [82]. While our results have shown that the distribution and abundances of Crenarchaeota and Euryarchaeota throughout Heron Island Reef are not uniform, there is still much to be learnt about the roles that Archaea play on coral reefs.…”
Section: Taxonomymentioning
confidence: 47%
See 1 more Smart Citation
“…Among the Crenarchaeota, which are often the dominant archaeal group in marine samples, Thermoprotei was the only class represented and accounted for only 0.03 % of sequences. This phylum includes members that have previously been shown to form associations with coral [82]. While our results have shown that the distribution and abundances of Crenarchaeota and Euryarchaeota throughout Heron Island Reef are not uniform, there is still much to be learnt about the roles that Archaea play on coral reefs.…”
Section: Taxonomymentioning
confidence: 47%
“…Recently, it has been demonstrated that the 16S rRNA sequences of coral-associated Archaea on Heron Island, the Gulf of Eilat and the Virgin Islands are more than 97 % similar [82]. Our results demonstrate that at a finer scale, the distribution and diversity of Archaea is not uniform across Heron Island Reef.…”
Section: Taxonomymentioning
confidence: 48%
“…Within coral reefs, nitrogen is often a limiting nutrient in the water column (Thomas and Owen, 1971;Crossland et al, 1984;Moore et al, 2013), as nitrate and ammonium concentrations are often o2 mM (Crossland et al, 1984;Bythell, 1990). However, ammonium and other inorganic nutrients are likely to be generated as metabolic by-products in the coral holobiont (Kawaguti, 1953;Muscatine and D'Elia, 1978;Siboni et al, 2008), and ammonium levels can reach up to 50 mM within coral mucus (Wild et al, 2005). Therefore the ability to use chemotaxis to exploit elevated levels of inorganic nutrients near the surface of corals may provide a competitive advantage for some coral reef bacteria.…”
Section: Sandy Substratementioning
confidence: 99%
“…To date, most reports on coral-bacterial interactions have focused on pathogens (reviewed in Harvell et al, 2007). However most bacterial-coral associations are likely to be advantageous, providing essential nutrients for the coral host (for example, nitrogen) (Wegley et al, 2007;Siboni et al, 2008;Rypien et al, 2009;Vega-Thurber et al, 2009) or protecting the coral from infection by producing antimicrobial agents that restrict the growth of potential pathogens (Loya et al, 2001;Ritchie, 2006;Shnit-Orland and Kushmaro, 2009). An interesting hypothesis that was recently presented, and that took into consideration the dynamic relationship between symbiotic microorganisms and corals under different environmental conditions, is the coral probiotic hypothesis (Reshef et al, 2006).…”
Section: Introductionmentioning
confidence: 99%